Long-term follow-up and donor site changes evaluation in suction blister epidermal grafting done for stable vitiligo: A retrospective study - K T Ashique; Feroze Kaliyadan (Wolters Kluwer Medknow Publications, 2015)
Background: Suction blister epidermal grafting (SBEG) is one of the most commonly performed types of vitiligo surgery for stable vitiligo. The advantages of SBEG include cost-effectiveness and a relatively easier learning curve for the surgeon. Aims: To evaluate the outcome in terms of both recipient and donor site changes, on long-term follow-up of the patients who underwent SBEG in our center. Methods: Thirty patients, 21 females and 9 males ages ranging from 9 to 55 years, all having either stable vitiligo not responding to medical line of treatment, were included in the study done which involved a variable follow-up period ranging from 2 to 62 months (mean 23.6, standard deviation 17.79). SBEG was done as day care procedure. The patients were reviewed after 1-week and thereafter followed-up in the subsequent months and years. The results of the procedures were graded as poor (0-24%), fair (24-64%), good (64-94) and excellent (95-100%) depending on the patient satisfaction. Donor site changes were also analyzed. Results: The face and lips showed an excellent result and color match and persistent pigment retention. The larger areas, especially the lesions on the limbs showed comparatively less response. Of the total, 6.7% showed poor, 13.3% fair, 30% good and 50% excellent response to treatment. Patient satisfaction wise, 53.3% of the patients were very happy, 26.7% were happy, 10% satisfied and 10% unhappy. Significant positive correlation between patient satisfaction and physician observation was seen (Spearman's rho 0.866). Conclusions: In spite of recent advances in surgical modalities like cellular grafting, SBEG continues to be a good, cost-effective, surgical method of treating vitiligo especially on the face and lip. The donor site also tends to show good healing tendency with minimal scarring and postinflammatory pigmentation.